Comparison of Collagen Fiber and Callus Deposition on Geopolymer-Carbonated Hydroxyapatite Nanocomposite Doped with Magnesium and Strontium on Days 14 and 28 Using Masson's Trichrome - Sutanto, Dahlia; Naliani, Silvia; Lucretia, Teresa (European Journal of General Dentistry, 2025)
This study aimed to evaluate collagen fiber deposition and callus formation on geopolymer-carbonated hydroxyapatite (CHA) nanocomposites-doped with magnesium (Mg) and strontium (Sr) on days 14 and 28 in the tibia of New Zealand rabbits.Geopolymer-CHA-Mg-Sr nanocomposite samples with a diameter of 3 mm and a height of 6 mm were placed in the tibia of eight New Zealand rabbits. Experimental subjects were randomly divided into two groups to evaluate collagen fiber deposition and callus formation on days 14 and 28 histomorphologically.T-test was performed, and p < 0.05 was considered statistically significant using Minitab version 13.There was no significant difference in collagen deposition and callus formation on the geopolymer-CHA-Mg-Sr surface on days 14 and 28 with p-values 0.075 and 0.842, respectively.Geopolymer-CHA-Mg-Sr is biocompatible, bioinert, and osteoconductive, and its mechanical properties meet the dentin standard values for hardness, while the modulus of elasticity, compressive, and tensile strength meets the enamel standard values.
Keywords: collagen fiber deposition; callus; geopolymer-CHA-Mg-Sr; Masson's trichrome